(untitled) (Bangladesh Medical Journal, 2009)
Death is unnatural when caused permaturely against the order of nature by injury, position or other means of violence. Data on unnatural deaths may reflect the law and order situation in a particular area of jurisdiction. This study is concerned with pattern of unnatural deaths in Dhaka Medical College mortuary during 1996. We found 1725 (97%) cases of unnatural deaths by analyzing 1772 cases of deaths. Data gives 18.37% increment in unnatural deaths 77.28% was males and 22.71% females. The frequency pattern of unnatural deaths were 68.92% RTAs, 11.69% homicide, 08.00% suicide and 2.80 natural. Burn, electrocution and others comprise the rest 11.565 unnatural deaths. Males suffer 3.4X more unnatural deaths than females. But RTAs males were 5.31X, in homicide 11.40X, in suicide 1.70X respectively than females. In hanging, female were predominant (1.72X of male deaths). 21-40 years is the age group showing peak frequencies on different types of unnatural deaths though hanging showed peak on 11-20 years. Besides, 95.47% of the unnatural deaths were the Muslims, 4.25% were Hindu and .14% was Christians. Firearms were used in 29.40% cases, blunt weapon in 38.46% cases and sharp cutting weapon in 31.60% cases of homicides respectively. Key words: Unnatural Death, RTA, Homicide DOI: 10.3329/bmj.v38i2.3572 Bangladesh Medical Journal 38(2) 2009 44-47